Implementation of Character Education in the Community of Class II A Children in West Kalimantan - Sutrisno; Amelyadi; Tri Wahyuni; Almumtahanah; Mahin Ridlo Ronas; Lince Amalia (Edumedia Solution, 2025)
Character education is a system of instilling character values in school members that includes components of knowledge, awareness or willingness, and actions to implement these values toward God Almighty, human beings, and the environment. The lack of awareness to embody the values of Pancasila will lead to the degradation of the nation’s character, causing citizens to deviate from the Pancasila values that form the character of the Indonesian nation. This community service aims to understand character education based on Pancasila values through exemplary conduct and habituation. This service activity is based on a literature study or library research process. It involves providing trainings to residents of the Class IIA Juvenile Correctional Institution in West Kalimantan to obey rules, norms, customs, and laws, as well as to foster a spirit of togetherness in their environment, instill democratic attitudes among fellow residents, teach social concern, and avoid apathy, thereby forming positive character traits in them. The institution is located in Kubu Raya Regency, West Kalimantan. This activity is motivated by the obligation in the Catur Darma Perguruan Tinggi, which encourages lecturers and students to be directly involved in community service. The methods used in this program include lectures, role-playing, discussions, and question-and-answer sessions. Through this approach, it is hoped that the residents will understand the importance of character education and will later possess sufficient awareness and knowledge to actively participate in social and national life upon returning to their communities.